Patient‐Controlled Remifentanil Analgesia as Alternative for Pethidine with Midazolam During Oocyte Retrieval in IVF/ICSI Procedures: A Randomized Controlled Trial. Issue 5 (12th April 2014) - Lier, Marit C.; Douwenga, Wieteke M.; Yilmaz, Fatos; Schats, Roel; Hompes, Peter G.; Boer, Christa; Mijatovic, Velja
Abstract Background Pethidine with midazolam‐induced conscious sedation for pain relief during transvaginal oocyte retrieval for in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) procedures is associated with residual pain and oversedation. Patient‐controlled analgesia (PCA) with remifentanil may serve as an alternative for pethidine. We investigated whether PCA remifentanil with diclofenac was associated with improved periprocedural pain relief than pethidine analgesia during IVF/ICSI procedures, with sedation scores, safety profiles, and patient satisfaction as secondary endpoints. Methods Seventy‐six women were randomized to receive pethidine (2 mg/kg i.m.) and midazolam (7.5 mg)‐induced conscious sedation (n = 40) or PCA with remifentanil and diclofenac (50 mg; n = 36). The Numeric Rating Scale, McGill Pain Questionnaire (MPQ), Ramsey Sedation Scale, and a 5‐day pain‐and‐discomfort diary were used to evaluate pain and sedation levels. Results There were no differences in baseline characteristics and reproductive outcomes between both groups. Periprocedural pain scores were comparable for remifentanil and pethidine groups (4 [3 to 7] vs. 6 [4 to 8]; P = 0.13). Pain scores in the pethidine group were significantly lower at 30 minutes after the procedure (1 [0 to 3] vs. 2 [1 to 5]; P = 0.016), but at cost of higher sedation levels when compared to remifentanil (4 [2 to 4] vs. 2 [2 to 2]; P < 0.001). Patient satisfaction was higher, and MPQ scores were lower in the remifentanil group. There were no differences in safety profiles between both analgesics. Conclusions Patient‐controlled analgesia with remifentanil showed a similar reduction in pain scores than pethidine with midazolam during oocyte retrieval, while pethidine induced the highest pain relief after the procedure. However, PCA remifentanil was associated with less sedation and a better patient satisfaction profile than pethidine.